2022
DOI: 10.3390/ijerph191811771
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester of Pregnancy as the Sensitive Period for the Association between Prenatal Mosquito Coil Smoke Exposure and Preterm Birth

Abstract: Mosquito coils are efficient mosquito repellents and mosquito coil smoke (MCS) contributes to indoor air pollution. However, no prior population-based study has investigated whether prenatal MCS exposure is a risk factor for preterm birth (PTB) and whether exposure to MCS in different trimesters of pregnancy is associated with different levels of risk. The sample involved 66,503 mother–child dyads. Logistic regression models were used to examine the relationships between prenatal MCS exposure during different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Pyrethroids are extensively used worldwide as commercial and household insecticides (Liu et al 2022). Continuous inhalation of mosquito coil smoke containing pyrethroid may harm the hearts of both young and adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrethroids are extensively used worldwide as commercial and household insecticides (Liu et al 2022). Continuous inhalation of mosquito coil smoke containing pyrethroid may harm the hearts of both young and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethrin/pyrethroids are the most widely used active ingredients of mosquito coils that were believed to have low toxicity in humans and untargeted animals (Li et al 2016). However, recent studies showed adverse effects of these components on human and animal wellness (Hassan et al 2019;Liu et al 2022; Badr and Vornanen 2023). Mosquito coils are generally manufactured from materials such as sawdust, coconut shell powder, wrappings, dyes, oxidants such as nitrate, and other additives that control smoldering (Pierre et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroids are extensively used worldwide as commercial and household insecticides (Liu et al 2022 ). Continuous inhalation of mosquito coil smoke containing pyrethroid may harm the hearts of both young and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethrin/pyrethroids are the most widely used active ingredients of mosquito coils that were believed to have low toxicity in humans and untargeted animals (Li et al 2016 ). However, recent studies showed adverse effects of these components on human and animal wellness (Hassan et al 2019 ; Liu et al 2022 ; Badr and Vornanen 2023 ). Mosquito coils are generally manufactured from materials such as sawdust, coconut shell powder, wrappings, dyes, oxidants such as nitrate, and other additives that control smoldering (Pierre et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%